Investigation of Genetic Diversity in Durum Wheat Germplasm Based on Grain Yield and Some Agronomic Traits - peyman ebrahimi; Ezzat Karami; َAlireza Etminan; Reza Talebi; Reza Mohammadi (پژوهشنامه اصلاح گیاهان زراعی, 2023)
Extended Abstract Introduction and Objective: Durum wheat (Triticum turgidum subsp. durum) also called macaroni wheat is a tetraploid species of wheat that has been improved during consecutive selection processes in Emmer wheat. Hence, it seems that a high level of genetic diversity exists in its germplasm and it can serve as an ideal gene pool for the improvement of cultivated varieties. The main objective of this study was to evaluate genetic diversity in a set of durum wheat genotypes in terms of grain yield and some agronomic traits. Materials and Methods: In this research, 94 durum wheat genotypes were investigated at the country's dryland agriculture research station in Serarud, Kermanshah, in the form of an augmented design with six repeated controls during two crop years 2016-2017 and 2017-2028. To study the genetic diversity of the studied genotypes agronomic traits such as the number of days to heading, number of days to physiological maturity, plant height, 1000-kernals weight, and grain yield were measured. After collecting experimental data, analysis of variance was done based on the best linear unbiased estimation (BLUE) models. The GT-biplot method was used to identify the superior genotypes based on grain yield and other traits. Results: The results showed that the genotypic effect was significant for all measured traits in both years (except for grain yield for the first year). The estimated genotypic variance for each of the measured traits was high in both agronomic years. According to the results obtained from the comparison of the genotypes' mean, it was found that genotypes numbers 24, 80, and 83 were relatively superior to other genotypes in terms of grain yield and other agronomic traits. Also, the results of GT analysis indicated the existence of a higher level of genetic diversity in terms of measured traits. As another result of this study, grain yield positively and significantly correlated with 1000-kernel weight. Conclusion: In general, according to the results obtained from this research, a high level of genetic diversity was found for grain yield and other measured traits in the investigated durum wheat genotypes, so this genetic diversity can be used in breeding programs to improve yield performance. Moreover, it seems that some selected genotypes for grain yield and other agronomic traits can be exploited for the simultaneous improvement of more than one trait in crossbreeding programs.